Avaliação de riscos teratogênicos em gestações expostas ao misoprostol : um estudo de caso-controle - Opaleye, Emérita Sátiro (2006)
Misoprostol (Cytotec®) is a prostaglandin E1 analog, previously commercialized with therapeutic purposes, with proscribed use in the gravid due to the risk of miscarriage. The common practice of abortion and the inefficient control on access to drugs in our country has lead to the generalized use of this drug as an abortive method. Studies have shown that the abortive potency of misoprostol is variable and its use without medical assistance may lead to thriving gestation, and a consequent risk of malformation to the fetus. Various case reports and epidemiological studies associate the use of misoprostol during gestation with offspring bearing malformations, especially with the Möebius sequence, terminal transverse-limb defects and diverse other anomalies of the central nervous system. The risk of acquiring these malformations cannot however be determined with available data, thus, there is a need for continuous research. OBJECTIVE: Identifying newborns bearing malformations in the leading maternities in Fortaleza and selecting their respective study controls, determining the frequency of exposition to misoprostol and identifying the spectrum of anomalies in the exposed group. METHODS: A case control-study, with a daily active search within the four largest maternities in Fortaleza, Ceara for newborn with congenital defects and a paired control, from July to November 2005. Every mother was interviewed with a questionnaire in the search for diverse expositions during pregnancy, including misoprostol. RESULTS: The groups were homogenous in respect to their socioeconomic profile and other main characteristics. Differences were found in respect to unfavorable outcomes among newborn with congenital defects like low weight (p=0,0001), low weight in relation to gestational age (p=0,006), increased natimortality (p=0,024) and increased perinatal mortality (p=0,0001). Both groups had adequate pre-natal assistance (69%), deferring only in the amount of ultrasonographic exams carried out in the case group (p=0,003). In regards to risk factors, the only deference encountered was the case group having more breech presentation (19,8%, p=0,037). Approximately 84% of mothers had been exposed to at least one medication during gestation, and the average number of drugs consumed was 3, 72. The use of tobacco, alcohol and illicit drugs was rarely informed, and only tobacco smoking was more frequent in the control group (p=0,0171). Most gestation were reported as planed or desired (70% of the total). Attempted abortion was reported in 6,8% of whole sample, with the use of misoprostol in the case group, although without statistic significance. CONCLUSION: The findings of these study suggest that exposition to misoprostol during gestation occurs more frequently in newborn with congenital defects compared with healthy ones, Odds Ratio (OR) = 3,65 [IC95%: 0,74;17,91]. The spectrum of malformations found and associated with misoprostol was hydrocephalus, meningomyelocele, agenesis of hip, equinovarus, luxation of the knee, hip congenital dislocation, absence of distal phalanges, syndactyly, polidactyly, anal imperforation, criptorchidism and cystic higroma.